Determinants of household earnings inequality: The role of labour market trends and changing household structure - Wen-Hao Chen; Michael Förster; Ana Llena-Nozal (Luxembourg Income Study (LIS), 2013)
This article assesses various underlying driving factors for the evolution of household earnings inequality or 23 OECD countries from the mid-1980s to the mid-2000s. There are a number of factors at play. Some are related to labour market trends - increasing dispersion of individual wages and changes in men's and women's employment rates. Others relate to shifts in household structures and family formation - more single-headed households and increased earnings correlation among partners in couples. The contribution of each of these factors is estimated using a semi parametric decomposition technique. The results reveal that marital sorting and household structure changes contributed, albeit moderately, to increasing household earnings inequality, while rising women's employment exerted a sizable equalising effect. However, changes in labour market factors, in particular increases in men's earnings disparities, were identified as the main driver of household earnings inequality, contributing between one-third and one-half to the overall increase in most countries. Sensitivity analysis applying a reversed-order decomposition suggests that these results are robust.
Keywords: D31; J12; J22; I30; 330; earnings inequality; assortative mating; female labour supply; decomposition; Haushaltseinkommen; Alleinerziehende; Weibliche Arbeitskräfte; Männliche Arbeitskräfte; OECD-Staaten